SYNTHESIS OF NOVEL NEONICOTINOIDS DERIVATIVES - juan pablo González-Gutiérrez; Silvana Moris; Claudio Barrientos (Journal of the Chilean Chemical Society, 2023)
Neonicotinoid compounds have been used as insecticides since the 1990s to effectively control Hemipteran pests such as aphids, leafhoppers, whiteflies, and additionally, for their lethal activity and low toxicity in humans. The synthesis of novel neonicotinoids compounds was achieved using (S)-(-)-(1-methyl-2-pyrrolidinyl)methanol and (±)-2-(1-methyl-2-pyrrolidinyl)ethanol with nitrobenzoyl chlorides derivatives in diethyl ether at room temperature to concentrate in vacuum to subsequently neutralize (pH = 8) with 7.4% (w/v) isopropanol HCl solution to obtain hydrochloride salts. (S)-(1-methyl-2-pyrrolidinyl)methyl and (±)-2-(1-methyl-2-pyrrolidinyl)ethyl 2-nitrobenzoate salts was not possible to form.